Panel MCC-300 Sebagai Alat Pengontrol Mesin Pompa Distribusi Air Bersih di Spam Perumdam Tirta Madani Kota Serang - Yunita Yunita; Mohammad Fatkhurrokhman (Fakultas Teknik Universitas Cenderawasih, 2023)
The Motor Control Center (MCC) Panel is a collection of components that become the control center in the operation of a three-phase electric motor with a larger capacity used as a clean water distribution pump machine. In this study has several objectives, including namely 1). Knowing the process of the Drinking Water Supply System (SPAM) in Perumdam Tirta Madani Serang City, 2). Knowing the working system of the MCC-300 Panel as a controller for the distribution machine at Perumdam Tirta Madani, Serang City, 3). Knowing how to maintain the MCC-300 Panel and clean water distribution machines at Perumdam Tirta Madani, Serang City. The methods used are observation, interviews, documentation and literature study. Prumdam Tirta Madani Serang City has several components in the clean water supply system, including raw water components, raw water transmission components, production unit components, and distribution unit components. In the working system the MCC-300 Panel consists of two blocks and there are other components contained in the panel. Then maintenance is carried out on the MCC-300 Panel and Distribution Machine, namely planned maintenance starting from cleaning to carrying out tests on components and machines using an electric meter.